Распределение личинок хирономид в рыбоводном пруду - Pотовская, В.C.; Шпет, Г.И. (Гидробиологический журнал, 1966)
Задачей настоящей работы было изучение единовременного распределения донных хирономид по всей площади пруда, имеющего различные биотопы, с целью более точной ориентировки в колебаниях их численности в этих биотопах. Такие данные могут быть использованы для более правильного суждения о кормовых ресурсах водоема. Для исследования был избран пруд «Карачун» площадью 1,9 га, расположенный в долине небольшой речки опытного рыбного хозяйства «Пуща-Водица» (в окрестностях Киева). The forest pond «Karachun», located on the border of the forest and forest-steppe belts, contains four basic biotopes with respect to the nature of the bottom deposits and depending on the depth. These biotopes are soft black silt (medial); silt with a considerable admixture of vegetable detritus (apex); sodded soil (right and left bank); clean sand (area of the dam). The benthos in the pond was sampled at approximately equal distances from 8 to 10 June 1964. A total of 100 bottom samples were taken, 25 in each biotope. A study of the instantaneous distribution of benthic Chironomidae larvae showed that it is extremely non-uniform with respect to both specific composition and quantity. The highest quantitative development is attained on silt and on silt with a considerable admixture of detritus (biomass—17.9 and 14.8 g/m2 respectively, numbers — 3785 and 3166 specimens per m2). The quantitative development of the larvae on sand is almost 50% less (9 g/m2 and 1750 specimens per m2). The most sparsely populated was sodded soil, where the biomass of the larvae did not exceed 2.0 g/m2, and the numbers 385 specimens per m2. The dominant role in all biotopes was that of Chironomus larvae (forms thummi and plumosus). The maximum specific diversity of Chironomidae was observed on silt with an admixture of vegetable detritus (17 forms) and on sodded soil (12 forms.) Sandy soil proved to be poorest in number of species (2 forms).